(untitled) (مجلة العلوم الشاملة, 2025)
Anemia is known to be a common and clinically important cause of chronic kidney disease (CKD) With the progression of CKD, various factors can be attributed to a reduction in hemoglobin (Hb) levels, the method used in this research is analytical it is a cross-sectional type of research, which means that it has been conducted throughout a certain time with a specific population sample, The temporal scope of the research was conducted from September to December 2023, whereas the spatial scope was meant to allocate the place where the research was done, which is in Training Hospital Al-khums city , Libya. the sample was selected according to the medical history of the patients and only included those who have CKD ,The number of this sample was 200. There most of patient were 118 males and 82 females.and the age 51 to 60 year and level of hemoglobin (Hb) is almost patient is under low average, all the data items are valid and reliability statistics, Cronbach’s alpha is > 0.01, however Urea and level of creatinine almost the patient’s high average ,Blood glucose almost all the patients have a high average in the WBC the normal averages In the RBCs number of normal averages is lower than the high average from all population samples the test on blood platelets in the results are almost average for normal almost all patients who have anemia are directly affected by CKD.